2013
DOI: 10.1007/s10068-013-0221-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimized astaxanthin production in Chlorella zofingiensis under dark condition by response surface methodology

Abstract: In this study, the major factors affecting both cell growth and astaxanthin production of Chlorella zofingiensis under dark were identified and optimized through statistical methods. A Plackett-Burman design was initially used to evaluate seven culture factors, of which glucose, NaNO 3 , and MgSO 4 ·7H 2 O were found to be the most important in affecting C. zofingiensis. The central composite design and response surface methodology (RSM) were further used to optimize these factors. The optimized glucose, NaNO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Statistical analysis has been applied on algal biomass and lipid production a lot, because it is an efficient way to optimize complex and various culture conditions including nutrient, temperature, pH and so on 2224 . However, statistical optimizations were limited to phototrophic cultivation of microalgae, and the application for heterotrophic cultivation has been seldom reported.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis has been applied on algal biomass and lipid production a lot, because it is an efficient way to optimize complex and various culture conditions including nutrient, temperature, pH and so on 2224 . However, statistical optimizations were limited to phototrophic cultivation of microalgae, and the application for heterotrophic cultivation has been seldom reported.…”
Section: Introductionmentioning
confidence: 99%
“…High glucose and low nitrate are optimal for astaxanthin production in batch cultures [ 89 , 91 ], although a higher astaxanthin yield of 11.14 mg/L was obtained from fed-batch culture with a combined glucose–nitrate mixture [ 91 ]. Moreover, a two-stage heterotrophic strategy where the media changed from 46.7, 1.13, and 0.125 g/L to 35.2, 0.281, and 0.023 g/L glucose, nitrate, and MgSO 4 ·7H 2 O, respectively, revealed that the highest astaxanthin yield (0.96 mg/g or 15.1 mg/L) was 74% higher than that in standard media [ 29 ]. After fermentation with 20 g/L glucose, the highest astaxanthin content reported was 73.3 mg/L or 0.07% DW at a cell density of 98.4 g/L which was considered to be comparable and even higher than quantities achieved from H. pluvialis [ 101 ].…”
Section: Effect Of Culture Conditions Stress and Trophic Mode On Cell...mentioning
confidence: 99%
“…C. zofingiensis is one of the most commonly mentioned microalgal species for implementation into a biorefinery [ 5 , 9 , 16 , 17 , 29 ]. However, despite being used as an example, limited experimental research has taken place to obtain multiple products.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorella zofingiensis optimized the Basal medium using a Plackett-Burman design to peruse seven different factors in which glucose, sodium nitrate and magnesium sulfate heptahydrate were identified to maximize both cell growth and astaxanthin production (Chen &Wang, 2013).…”
Section: Determination Of Carotenoid Concentration and Statistical Analysismentioning
confidence: 99%